2018
DOI: 10.1101/275925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age differences in head motion and estimates of cortical morphology

Abstract: 12Head motion during MRI scanning influence estimates of cortical morphology. 13 Previous studies have found that older adults demonstrate greater head motion than 14 younger adults, while other studies have found task-related differences in head motion. 15Cortical morphology also differ with age, as measured by cortical thickness, fractal 16 dimensionality, and gyrification. Here I replicated all three of these prior findings 17 within a larger dataset than these results have been demonstrated previously, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…In broad strokes, our findings concur with previous studies which have demonstrated a connection between motion metrics and age and/or BMI (Madan, 2018;Savalia et al, 2017). However, true (lower frequency) head motion may also be correlated with these demographic characteristics, even when HFmotion is explicitly removed (Siegel et al, 2017), suggesting that some participant characteristics may relate to both true and factitious motion.…”
Section: Implications For Studies Across Diverse Populationssupporting
confidence: 90%
See 1 more Smart Citation
“…In broad strokes, our findings concur with previous studies which have demonstrated a connection between motion metrics and age and/or BMI (Madan, 2018;Savalia et al, 2017). However, true (lower frequency) head motion may also be correlated with these demographic characteristics, even when HFmotion is explicitly removed (Siegel et al, 2017), suggesting that some participant characteristics may relate to both true and factitious motion.…”
Section: Implications For Studies Across Diverse Populationssupporting
confidence: 90%
“…Head motion introduces bias in measured FC through both common effects across all pair-wise regional correlations as well as distance-dependent biases, where correlations are increased most for adjacent regions and relatively decreased for regions that are distant (Power et al, 2012;Satterthwaite et al, 2012). These distortions are of particular concern in studies comparing groups or conditions that differ systematically in head motion, for example in comparisons between children and young adults (Greene et al, 2016;Nielsen et al, 2019;Satterthwaite et al, 2013), adults of different ages (Madan, 2018;Savalia et al, 2017), or clinical populations vs. normative controls Fair et al, 2012;Gratton et al, 2019). Fortunately, effective approaches have been developed to reduce biases introduced by head motion (Power et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While our estimate of a weight loss‐induced bias in neuroimaging outcomes (i.e., 5% increase in total gray matter volume after bariatric surgery) relied on between‐subject estimates of the effect of head motion (Alexander‐Bloch et al, ) and therefore has to be interpreted with caution, this finding still stresses the importance to control for head motion differences in future MRI analyses. Different techniques, such as multi‐echo sequences (Power et al, ), fixation through head molds (Power et al, ) and tactile feedback during scanning (Krause et al, ) have been proposed to considerably reduce head motion a priori — which is probably the best way to handle this important confound for practically all imaging outcomes (Baum et al, ; Beyer et al, ; Madan, ; Reuter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this pre‐registered analysis (https://osf.io/epsxt), we therefore aimed to test whether a radical weight‐loss intervention (bariatric surgery) compared to a control group induces consistent changes of head motion during magnetic resonance imaging (MRI) in obese individuals. In addition, we aimed to estimate the confounding effects of a potential change in head motion after bariatric surgery on structural brain measures, according to previous literature (Madan, ; Reuter et al, ; Savalia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While a few studies have reported decreased OFC gray matter volume [13][14][15] and decreased cortical thickness 16 in pathological gamblers compared with healthy controls, other studies have failed to report significant group differences [17][18][19][20] . These inconsistencies might reflect the influence of factors such as age, comorbidities and head motion acting as confounds on structural brain measures 21 , as well as the heterogeneity existing among gamblers, as suggested by a recent study which found decreased OFC gray matter volume specifically in gamblers showing low risk-taking 22 . As a matter of fact, structural abnormalities observed in pathological gamblers are less consistent and of more modest magnitude than those reported in substance addiction 19,20,23 .…”
Section: Introductionmentioning
confidence: 99%